FAKTOR-FAKTOR GAYA HIDUP YANG BERHUBUNGAN DENGAN OBESITAS ANAK SEKOLAH DASAR SWASTA BERNARDUS DAN HJ ISRIATI KELAS 4-6 DI SEMARANG - Griska Erfiana Nilasari; Henry Setiawan Susanto; Arie Wuryanto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2015)
Obesity in children is a complex problem. Currently, excessive nutrients and obesity is an epidemic in Australia, New Zealand and Singapore and rapidly spread in the population of Pacific islands and in a certain Asian country. Obesity can result in varied chronic diseases. The purpose of this case control study is to find out the relation of pattern of heredity, consumption, and physical activity, to the incident of obesity in the students of elementary school Bernardus and Hj Isriati in Semarang. The samples for this study were (72 students for case group and 72 students for control group) from grades 4-6 from Bernardus and Hj Isriati elementary schools selected through quota sampling technique. The data obtained were analyzed by using univariate and bivariate. The results of study shows that there is a significant influence between IMT of parents (OR =8,13 ), exercise habits (OR =9,83 ), the habit of playing game (OR =4,28), the habit of eating fast food (=15,78), the habit of drinking soft drink (OR = 6,79), and the habit of eating fruits and vegetables (OR = 2,7 ) and the incident of obesity in the students of elementary students in Bernardus and Hj Isriati schools in Semarang.